Active Learning Small Group Discussion Method to Improve the Quality of Islamic Education Learning - Teguh Ilmawan; Tumin (Journal of Islamic Education, 2024)
This study aims to analyze the process of improving the quality of learning in the scope of Islamic religious education. This study uses a qualitative approach, field studies. Data were collected through interviews, observations, and documentation. The collected data were checked with source triangulation and technique triangulation then analyzed with the stages of data condensation, data presentation, and drawing conclusions. The results of the study indicate that the small group discussion method encourages collaboration, because students are divided into several groups, thus encouraging collaborative learning. This approach encourages active involvement and empowers students, which leads to improving the quality of Islamic religious education learning. Active learning methods improve the quality of learning through increasing participation and learning motivation, increasing conceptual understanding, the role of teachers as facilitators and developing social skills and critical thinking. The implementation of the sgd method needs to be applied more widely, both in Islamic religious education subjects and other subjects, to continue to encourage more effective and meaningful learning for students.